STRATEGI KONSELING PASTORAL SEBAGAI UPAYA KESEJAHTERAAN PSIKOLOGIS (PSYCHOLOGICALL WELL-BEING) BAGI IBU GENERASI SANDWICH YANG BEKERJA - Frieska Putrima Tadung; Charga Jofial Rumate (POIMEN Jurnal Pastoral Konseling, 2023)
The term "sandwich generation" refers to a group of individuals who find themselves in a situation where they face simultaneous demands to care for their elderly parents and their dependent children, both physically and financially. The sandwich generation is closely linked to caregiving. It's not just about parenting their children; there are also caregiving demands coming from their parents. This dual role and responsibility often present various challenges, leading to negative impacts financially, physically, emotionally, and even psychologically. As the dynamics of these complex roles increase and the risk of experiencing stress due to caregiving responsibilities rises, individuals are likely to have lower psychological well-being. The higher the level of stress experienced by the sandwich generation, the lower their psychological well-being tends to be. In this context, an approach that can be taken is to provide pastoral counseling services to address cases of low psychological well-being among mothers in the sandwich generation, impacting their mental health. Counseling is an effort used to resolve problems, a process where a counselor provides assistance or guidance to the individual (counselee) through psychological approaches, direction, or education, with the hope that the individual can understand their own abilities to resolve various issues.